Effect of barnacles on the survival and growth of temperate mangrove seedlings - S. Satumanatpan (2018)
Loss of mangrove forests is a problem in many areas of the world, and attempts to reestablish seedlings have been hindered by slow growth rates and low seedling survival. This poor seedling performance has, in part, been attributed to the presence of barnacles attached to stems and leaves of mangroves. There is, however, little experimental evidence to assess the importance of these fouling organisms. In Western Port, a large bay in southeastern Australia, the only species of mangrove, Avicennia marina, is heavily fouled by a single barnacle species, Elminius covertus. We tested whether barnacles influenced seedling growth and survival of A. marina by removing them from the stem, upper, and lower leaf surfaces, in all combinations. Seedlings were then followed for 2 yr and measured at quarterly intervals. Survival of mangrove seedlings over the 2 yr period did not depend on the presence of barnacles on any surface. Seedlings grew mainly in late spring and summer, increasing in height and number of leaves. The presence of E. covertus on seedlings of A. marina did not have a significant negative effect on their growth, although the experiment was capable of detecting subtle differences in growth with high power. It is suggested that other factors, such as a dense cover of algae or seagrasses, smothering by sediments, and damage by herbivores, as well as unfavorable climatic conditions, are stronger influences than barnacles on the survival and growth of seedlings of A. marina.